Within‐plant variation in defences in response to simulated herbivory in a semi‐arid southern African savannah. (21st January 2015) - Sebata, Allan; Ndlovu, Lindela R.
Abstract: Within‐plant spatial variation in herbivore pressure can induce localized antiherbivory defence responses. We tested this hypothesis by studying branch‐specific responses of Acacia robusta, Dichrostachys cinerea and Ziziphus mucronata to simulated mammalian herbivory. Herbivory was simulated by clipping the terminal shoots (3 cm from tip) of tree branchlets, allowing them one year of regrowth and then comparing their spine length and density and condensed tannins with those of adjacent unclipped branchlets. Condensed tannins concentrations were higher in clipped branchlets than in unclipped branchlets in all three woody species ( P  < 0.05). Spine length was higher in clipped branchlets than in unclipped branchlets in A. robusta ( P  < 0.05) but was similar in both D. cinerea and Z. mucronata ( P >  0.05). Spine density was double in clipped branchlets as compared to the unclipped branchlets in Z. mucronata ( P  < 0.05) but was similar in both A. robusta and D. cinerea ( P  > 0.05). We found evidence of within‐plant variation in condensed tannins concentration and spine length and density in response to simulated herbivory in the three woody species.